Using learning analytics to assess student engagement and academic outcomes in open access enabling programmes. (4th May 2017) - Atherton, Mirella; Shah, Mahsood; Vazquez, Jenny; Griffiths, Zoe; Jackson, Brian; Burgess, Catherine
ABSTRACT: Curriculum design, teaching methods, assessments and range of academic support need to be inclusive in Open Access Enabling courses. The findings of this study confirm a correlation between student access to online learning materials and a positive impact on grades in science courses. More specifically, students who frequently use the online learning system to access materials have better assessment and exam results.